Malfunction of Vascular Control in Lifestyle-Related Diseases: Oxidative Stress of Angiotensin II-induced Hypertension: Mitogen-Activated Protein Kinases and Blood Pressure Regulation - Shoji Kimura; Guo-Xing Zhang; Youichi Abe (Elsevier, 2004)
The candidate mechanisms for maintaining hypertension in a chronically angiotensin II (Ang II)-infused state include direct vasoconstriction of the vasculature, disturbance of renal water/sodium handling, and central/peripheral sympathetic nerve regulation of hemodynamics. The involvement of reactive oxygen species (ROS) has been studied in these proposed mechanisms and the importance of ROS in progression of Ang II-induced hypertension has been accepted. We recently reported ROS-sensitive blood pressure regulation in chronically as well as acutely Ang II-infused hypertensive rats. The facts suggested that mechanisms for maintaining high peripheral vascular resistance in chronically Ang II-infused hypertensive rats were different from those involved in the acute hypertensive response to Ang II from the perspective of ROS sensitivity and that there must be a time-dependent transition from ROS-non-sensitive to ROS-sensitive vasoconstriction during prolonged Ang II infusion. In this review, we introduced our recent work describing the time transition of ROS sensitivity in Ang II-induced hypertension and activation of cardiovascular mitogen-activated protein kinase (MAPK) in acute and chronic phases Ang II infusion in conscious rats. Keywords:: angiotensin, vasoconstriction, tempol, superoxide anion, mitogen-activated protein kinase